PENGARUH DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DAN PENDAPATAN ASLI DAERAH TERHADAP ALOKASI BELANJA MODAL - Sari, Dian Novita (Universitas Slamet Riyadi, 2015)
The purpose of this study was to analyze the significance of the influence of the General Allocation Fund, Special Allocation Fund and Regional Income partially or simultaneously to the allocation of capital expenditure on district / city in the province of Central Java. The results of the analysis we concluded that the General Allocation Fund partially no significant effect on the allocation of capital expenditure on district / city in Central Java province Period 2011 - 2013. While the Special Allocation Fund and Regional Income partially significant effect on the allocation of capital expenditures. The results of simultaneous analysis showed that the General Allocation Fund, Special Allocation Fund and Regional Income significant effect on the dependent variable is the allocation of capital expenditure on district / city in Central Java province Period 2011 - 2013. The results of the analysis of the value of the coefficient of determination obtained Adjusted R Square = 0.799 means it is known that the influence of the independent variables are given by the General Allocation Fund, Special Allocation Fund and Regional Income for the dependent variable is capex at Regency / City in Central Java Province Period 2011 - 2013 by 79,9 percent while the rest (100% - 79,9%) = 10,1 percent influenced by other factors beyond the variables studied. Keywords: General Allocation Fund, Special Allocation Fund, Local Revenue and capital expenditure